2016
DOI: 10.1190/geo2016-0110.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimation of intrinsic induced polarization and superparamagnetic parameters from airborne electromagnetic data

Abstract: The primary aim of my research is to improve the characterization of induced polarization (IP) responses in airborne electromagnetic (AEM) survey data. The principal objectives are to test alternative methodologies for quantitative modeling and inversion to extract the spatial variation of IP parameters using the inductively thin-sheet model. The methods tested first fit, by nonnegative least squares, an AEM decay to the early delay time data, using thin-sheet basis functions. This modeled AEM decay is assumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Inversion of the induction transients in terms of horizontally layered earth with σ * (ω) described by the Cole-Cole model has become a routine procedure (Kozhevnikov and Antonov, 2008;Kozhevnikov et al 2014;Seidel and Tezkan, 2017). In recent years, great progress has been made in the quantitative interpretation of airborne TEM surveys by taking into account the IP effects (Macnae 2015b(Macnae , 2016Viezzoli and Kaminski 2016). In recent years, great progress has been made in the quantitative interpretation of airborne TEM surveys by taking into account the IP effects (Macnae 2015b(Macnae , 2016Viezzoli and Kaminski 2016).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
See 2 more Smart Citations
“…Inversion of the induction transients in terms of horizontally layered earth with σ * (ω) described by the Cole-Cole model has become a routine procedure (Kozhevnikov and Antonov, 2008;Kozhevnikov et al 2014;Seidel and Tezkan, 2017). In recent years, great progress has been made in the quantitative interpretation of airborne TEM surveys by taking into account the IP effects (Macnae 2015b(Macnae , 2016Viezzoli and Kaminski 2016). In recent years, great progress has been made in the quantitative interpretation of airborne TEM surveys by taking into account the IP effects (Macnae 2015b(Macnae , 2016Viezzoli and Kaminski 2016).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…Some publications report on the inversion of TEM responses in terms of the three-dimensional distribution of frequency-dependent conductivity (Marchant et al 2013;Marchant, Haber and Oldenburg 2014). In recent years, great progress has been made in the quantitative interpretation of airborne TEM surveys by taking into account the IP effects (Macnae 2015b(Macnae , 2016Viezzoli and Kaminski 2016).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…Even though it was interesting from a scientific standpoint, extracting meaningful information from those negative data remained challenging at the time. This is still an area of active research (Kang and Oldenburg, 2015;Viezzoli et al, 2015;Macnae, 2016), and the processing and interpretation of airborne IP data will be addressed in the final study of this three-part series on TKC. For the remainder of this paper we shall work only with data that we feel are not severely contaminated with IP signals.…”
Section: Tem Datamentioning
confidence: 99%
“…Investigations presented here compare the theoretical sensitivity of inductive AIP using a concentric loop system operated at 25 or 30 Hz with galvanic ground IP operated at 0.125 Hz. Macnae (2016) and Macnae and Hine (2016) tested this model on VTEM data sets from Tasmania and New South Wales, and showed that allowing for AIP effects greatly improved the error of fit to the data, and provided coherent maps of the Cole-Cole IP parameters chargeability m IP , time constant τ IP and frequency dependence c.…”
Section: Introductionmentioning
confidence: 99%